Pengembangan Sumber Daya Manusia untuk Meningkatkan Kinerja Karyawan pada PT Insan Ki Angka - Yanti Apriyani; Aep Saefullah; Zubair Arza; Joned Ceilendra Saksana; Rahman Upe; Nurhayati Nurhayati; Idrisi Raliya Putra; Ranto Ranto; Tedi Supriadi; Moh Islah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
This community service aims to develop human resources to improve employee performance at PT Insan Ki Angka. This activity was carried out in November 2021, using training and development methods which included workshops, skills training and mentoring programs. This method is applied on an ongoing basis to ensure effective transfer of knowledge and skills to employees. The results of the activities show that human resource development through comprehensive and ongoing training can significantly improve employee performance, operational efficiency and job satisfaction. While there are challenges such as limited training time and variations in technology skills, the benefits are far greater. Therefore, it is recommended that companies continue to implement structured HR development programs and provide ongoing support for employees, as well as ensure that adequate facilities and resources are available to support the implementation of new knowledge. These steps will help the company achieve its vision and mission and strengthen its competitiveness in the market.